Public Relations : Potential and Prospects - Alauddin Masood (Islamabad Ahsen Publishing House, 1996)
This book Makes an inersting reading and would be of immense benefit for the general public and specialists. This book will help in planning and executing projection campaigns in a more professional, systematic and effective way using elements aptly pinpointed in diffferent chapters.
Include Index and Bibliography.
Keywords: Public Relations